Pengaruh Religiusitas dan Profit Margin terhadap Peningkatan Kuantitas Nasabah pada Bank Syariah - Hadiyan, Edwin (Budgeting: Jurnal Akuntansi Syariah, 2024)
The purpose of this paper is to determine the influence of religiosity and profit margins on increasing the number of private bank customers, both partially and simultaneously. This quantitative research was conducted using a sample of 183 respondents, selected through simple random sampling. The study utilized both primary and secondary data, collected via questionnaires, observations, and focus group discussions (FGD). The data analysis techniques included descriptive analysis, validity and reliability tests, classical assumption tests, hypothesis testing, multiple regression analysis, and both simultaneous and partial tests. The data was processed using the SPSS program.